1996
DOI: 10.1093/ee/25.6.1421
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serangium parcesetosum (Coleoptera: Coccinellidae) as a Biological Control Agent of the Silverleaf Whitefly (Homoptera: Aleyrodidae)

Abstract: The coccinellid predator from India, Serallgiwll pareesetoswll Sicard, was studied as a potential biological control agent of the silverleaf whitefly, Belllisia argelliifo/ii Bellows & Perring [also known as the sweetpotato whitefly, B. tahaci (Gennadius) Bio!)1,)e B]. Studies were performed on prey preference, and effects of host plant on predation, and temperature on life-histoty and predation rates. In one test, the predator was offered simultaneously 5 prey choices: corn earworm, Helieoverpa ;:;ea (Boddie)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 4 publications
1
39
0
Order By: Relevance
“…Previous studies have shown that different plant species can have profound effects on predation rates. In Serangium parcesetosum Sicard (Coccinellidae) feeding on B. argentifolii (Legaspi et al 1996), predation was highest on cucumbers, followed by tomato and cantaloupe, and lowest on hibiscus, which are similar to the results presented here. In the predatory stinkbug Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) feeding on 4 th instar Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae), attack rates were higher and handling times shorter on sweet pepper and eggplant, compared with tomato (De Clercq et al 2000).…”
Section: Performance On Plant Speciessupporting
confidence: 90%
“…Previous studies have shown that different plant species can have profound effects on predation rates. In Serangium parcesetosum Sicard (Coccinellidae) feeding on B. argentifolii (Legaspi et al 1996), predation was highest on cucumbers, followed by tomato and cantaloupe, and lowest on hibiscus, which are similar to the results presented here. In the predatory stinkbug Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) feeding on 4 th instar Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae), attack rates were higher and handling times shorter on sweet pepper and eggplant, compared with tomato (De Clercq et al 2000).…”
Section: Performance On Plant Speciessupporting
confidence: 90%
“…S. parcesetosum is recorded to be host specific to B. tabaci (Kapadia and Puri 1992)-This species also seems to be a specialist predator of whiteflies (Cohen et al 1995). When S. parcesetosum was offered simultaneously five prey choices, namely eggs of the corn earworm, Helicoverpa zea (Boddie) (Lep., Noctuidae) and eggs of the tobacco hornworm, Manduca sexta (L.) (Lep., Sphingidae), as well as eggs and early instars of B. argentifolii reared on poinsettia, cantaloupe and cucumber plants, S. parcesetosum adults did not feed on H. zea eggs and M. sexta eggs presented, indicating a preference for B. argentifolii (Legaspi et al 1996). This author further stated that predatory adults prefer to feed on B. argentifolii immatures regardless of the host plant.…”
Section: Discussionmentioning
confidence: 77%
“…S. parcesetosum was first reported on B. tabaci in India (Kapadia and Puri 1992) and in 1994 it was found attacking D. citri and B. tabaci in Syria (Abboud and Ahmad 1998). It has also been used against the silverleaf whitefly, Bemisia argentifolii Bellows and Perring, in the USA (Legaspi et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These include Serangium parcesetosum that feeds on eggs and nymphs of B. tabaci (Legaspi et al, 1996). B. tabaci pupae were more suitable prey for the development of S. parcesetosum larvae than nymphs and eggs, while pupae and nymphs were more suitable for the coccinellid females (Al-Zyoud & Sengonca, 2004).…”
Section: Conclusion and Discussionmentioning
confidence: 99%